2013
DOI: 10.1097/bpb.0b013e32836379c2
|View full text |Cite
|
Sign up to set email alerts
|

Rib osteoblastoma as an incidental finding in a patient with adolescent idiopathic scoliosis

Abstract: The purpose of this article is to present an unreported case of rib osteoblastoma associated with progressive adolescent idiopathic scoliosis and to discuss thoracogenic scoliosis as a potential cause of curve progression after tumor resection. An 11-year and 8-month-old girl with adolescent idiopathic scoliosis was referred with an incidental finding of an expansile lesion in the posterior left seventh rib. A computed tomography-guided needle biopsy established the diagnosis of benign osteoblastoma. Transarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
2
0
0
Order By: Relevance
“…It has been reported that osteoblastoma can accumulate 18 F-FDG, 6–10 which was consistent with the PET/CT manifestations in our patient. According to previous reports, most cases of rib osteoblastoma manifest as large masses with a certain space-occupying effect, and the tumor size is usually much larger than that of this patient 11–16 . The observations in this case expand our knowledge about the etiology of lesions in the ribs.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…It has been reported that osteoblastoma can accumulate 18 F-FDG, 6–10 which was consistent with the PET/CT manifestations in our patient. According to previous reports, most cases of rib osteoblastoma manifest as large masses with a certain space-occupying effect, and the tumor size is usually much larger than that of this patient 11–16 . The observations in this case expand our knowledge about the etiology of lesions in the ribs.…”
supporting
confidence: 63%
“…According to previous reports, most cases of rib osteoblastoma manifest as large masses with a certain space-occupying effect, and the tumor size is usually much larger than that of this patient. [11][12][13][14][15][16] The observations in this case expand our knowledge about the etiology of lesions in the ribs. Osteoblastoma should be considered in the differential diagnosis of unexplained focal lesions of the ribs on 18 F-FDG PET/CT in elderly patients.…”
supporting
confidence: 63%
“…The pediatric orthopaedic literature is replete with reports of incidental findings unrelated to the target diagnosis or pathology discovered on radiographs and other imaging modalities. 9,10 Complete radiographic evaluation of patients with presumed AIS includes not only the spine but also enough of the pelvis to determine the patient's Risser sign and the status of the tri-radiate cartilages. 8 To obtain images that provide this information, the hips are frequently imaged as well.…”
Section: Discussionmentioning
confidence: 99%